EXPLAIN THE CONTENT OF DEVELOPING AUTHENTIC ASSESSMENT INSTRUMENTS IN INDONESIAN LANGUAGE LEARNING VIII SMP NEGERI 2 BINJAI - Ayudia Helmi; Fitriani Lubis (Indonesian language and literature education program Majapahit Islamic University, 2024)
This study aims to, (1) develop the form of authentic assessment instruments in the learning news text of SMP Negeri 2 Binjai, (2) describe the process of developing authentic assessment instruments in the learning news text of grade VIII SMP Negeri 2 Binjai, (3) describe the feasibility of authentic assessment instruments in the learning news text of grade VIII SMP Negeri 2 Binjai. The type of research used in this research is research and development (R&D). The research instruments used in this study were material expert validation questionnaires, languages, and teacher response tests using the Likert scale. The results of this study proved that authentic assessment instruments in class VIII SMP Negeri 2 news text learning were included in the